'Visions of ecstasy': resilience and melancholy in the musical moments of Bande de filles (Céline Sciamma, 2014). Issue 3 (1st October 2020) - Pember, Alice
ABSTRACT: This article examines the politics of pop music in Céline Sciamma's Bande de filles ( Girlhood, 2014). Responding to feminist readings of Bande de filles 's most striking musical sequence (in which the protagonists lip-sync to Rihanna's 'Diamonds') as an expression of the protagonists' joyous defiance of the raced and gendered oppression that they face growing up in the Parisian banlieue, this article will instead situate it within the context of neoliberal resilience discourse. Easily mistaken for resistance, resilience is a neoliberal value that demands bodies 'bounce back' from the damage inflicted upon them by white supremacist capitalist patriarchy. Resilience, and its counter-resilient inverse melancholy, are political affects that operate through contemporary aesthetic forms. Following Robin James's reading of 'Diamonds' as a melancholic anthem that sonically circumvents resilient musical formations, this article suggests that this melancholic political affect complicates the joyous, resistant function that has been emphasised in other feminist readings. Contextualising this sequence within the musical landscape of some of the film's other musical moments, this article suggests that the critical over-emphasis on the resistance staged by the affective musical moment in Bande de filles overlooks the web of politically ambivalent meanings that music constructs in the film.